Balarama : A Royal Elephant - Lewin, Ted.; Lewin, Betsy (New York : Lee & Low Books, 2009)
World travelers Ted and Betsy Lewin recount how the trained elephants of southern India, in particular the one chosen to be the lead elephant in the Mysore Dasara, are raised, cared for, and prepared for performing in ceremonial processions.
Keywords: Asiatic elephants -- Mysore (India); Asiatic elephants -- Training; Nagarahole National Park (India)